2016
DOI: 10.1128/mbio.01714-16
|View full text |Cite|
|
Sign up to set email alerts
|

The Genome-Wide Interaction Network of Nutrient Stress Genes in Escherichia coli

Abstract: Conventional efforts to describe essential genes in bacteria have typically emphasized nutrient-rich growth conditions. Of note, however, are the set of genes that become essential when bacteria are grown under nutrient stress. For example, more than 100 genes become indispensable when the model bacterium Escherichia coli is grown on nutrient-limited media, and many of these nutrient stress genes have also been shown to be important for the growth of various bacterial pathogens in vivo. To better understand th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
61
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 59 publications
5
61
0
Order By: Relevance
“…To offset sub-optimal growth conditions, bacteria develop a number of different adaptation mechanisms, or "stress responses". These include, but are not limited to, dormant endospore formation, lowered metabolic rate, altered cell morphology [1], changes in gene expression [2], and protein synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…To offset sub-optimal growth conditions, bacteria develop a number of different adaptation mechanisms, or "stress responses". These include, but are not limited to, dormant endospore formation, lowered metabolic rate, altered cell morphology [1], changes in gene expression [2], and protein synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Nichols et al showed that yggS and glyA, encoding serine hydroxymethyl transferase, are a synthetic lethal pair in E. coli (6). Impaired growth of the yggS glyA double-knockout mutant was also identified in the genome-scale cross of the glyA mutant with the entire E. coli gene deletion collection (7). Later, it was found that the double mutant can grow in a synthetic medium supplemented with Gly (3), which indicated that the gene pair is a conditional lethal mutant.…”
mentioning
confidence: 99%
“…Briefly, the chloramphenicol resistance cassette from pKD3 was amplified by PCR with primers 5’-CAATTATTTTTACAAATTGATCAGCGCTAAATACTGCTTCACAACAAGGAGTAGGCT GGAGCTGC-3’and 5’-AGACCTACAAGGGCACAGGTCTGATAAGCGCAGCGCCAGCGAATAACTTACATATG AATATCCTCCTTAGTTCC-3’ and the resulting amplicon was transformed into electro-competent S . Tm SL1344 cells harboring the pSim6 plasmid as previously described 57,58 . Successful recombinants were confirmed by colony PCR using primers 5’CGACCATCTCCAGCAGCCAC-3’ and 5’GAAAAGGCGAGAATGCGGCG-3’.…”
Section: Methodsmentioning
confidence: 99%